2023
DOI: 10.1021/acsanm.3c00319
|View full text |Cite
|
Sign up to set email alerts
|

MnxWO4 Nanostructure-Based Catalysts for Single-Step Oxidation of Cyclohexane and Methane to Oxygenates

Abstract: Activation of the C−H bond in cyclohexane (CYH) and methane is a crucial step to obtain desirable oxygenated products using nanostructured catalyst and is a great challenge and an efficient route to mitigate the inauspicious effects of climate change. The active sites were identified using XRD, HR-TEM, SEM, N 2 sorption analysis, TPR, Raman, XPS, TGA, in situ DRIFT, XAS, etc. In optimal reaction conditions, 46% of CYH was converted into adipic acid (AA) on Mn x WO 4 nanostructures within 6 h. The recyclability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Prabu et al 94 employed the Mn x WO 4 nanostructured catalyst for the one-pot oxidation of cyclohexane to adipic acid (Fig. 8c).…”
Section: Aerobic Oxidation Of Alcoholsmentioning
confidence: 99%
“…Prabu et al 94 employed the Mn x WO 4 nanostructured catalyst for the one-pot oxidation of cyclohexane to adipic acid (Fig. 8c).…”
Section: Aerobic Oxidation Of Alcoholsmentioning
confidence: 99%
“…Aerobic oxidation of hydrocarbons is of great importance for producing value-added oxygenated chemicals in the modern chemical industry. , Among them, the selective oxidation of saturated alkanes under mild conditions is much more difficult due to the laborious activation of inert C–H bonds and facile deep oxidation of reactive target products. , For example, cyclohexane liquid-phase oxidation into cyclohexanol, cyclohexanone, and adipic acid, a typical hydrocarbon resource high-value utilization process, is the crucial technology to manufacture polyamide 6 and 6,6 in industry. , In general, the oxidation of cyclohexane with molecular oxygen is performed in the presence of soluble metal salts at the temperature of above 150 °C, wherein the cyclohexane conversion is controlled below 4% to maintain the overall selectivity toward cyclohexanol and cyclohexanone at a relatively high level of 70–85%. , The serious energy consumption and increased environmental concerns call for benign oxidation including high oxidation efficiency, recoverable catalysts, molecular oxygen as the green oxidant, and solvent-free. In the past decade, the solvent-free cyclohexane oxidation has been paid more attention in developing new types of heterogeneous catalysts. , Diverse metal and metal oxide catalysts have been developed and applied into the catalytic oxidation of cyclohexane. Among them, metallic cobalt and cobalt oxides (e.g., Co 3 O 4 , LaCoO 3 , and Co-MgAlO) with the adjustable structure properties are widely considered as the promising catalysts for the cyclohexane oxidation by adsorbing and activating O 2 molecules or C–H bonds in cyclohexane on the active sites. Nevertheless, Unnarkat et al and Yuan et al found that organic acids and water generated in the course of the cyclohexane oxidation were inclined to adsorb on the active sites, giving rise to the inevitable deactivation of the catalysts. , Thus, it can be found that there are two core issues to be addressed for the heterogeneous catalytic oxidation of cyclohexane: (i) to ensure the acceptable product selectivity (above 90%) at the relatively high conversion (above 15%) under mild reaction conditions and (ii) to construct the robust catalytic structure against the deactivation during oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 For example, cyclohexane liquid-phase oxidation into cyclohexanol, cyclohexanone, and adipic acid, a typical hydrocarbon resource high-value utilization process, is the crucial technology to manufacture polyamide 6 and 6,6 in industry. 5,6 In general, the oxidation of cyclohexane with molecular oxygen is performed in the presence of soluble metal salts at the temperature of above 150 °C, wherein the cyclohexane conversion is controlled below 4% to maintain the overall selectivity toward cyclohexanol and cyclohexanone at a relatively high level of 70−85%. 7,8 The serious energy consumption and increased environmental concerns call for benign oxidation including high oxidation efficiency, recoverable catalysts, molecular oxygen as the green oxidant, and solvent-free.…”
Section: Introductionmentioning
confidence: 99%